A system of coupled partial differential equations exhibiting both elevation and depression rogue wave modes. (September 2015) - Wu, C.F.; Chan, H.N.; Chow, K.W.
Abstract: Analytical solutions are obtained for a coupled system of partial differential equations involving hyperbolic differential operators. Oscillatory states are calculated by the Hirota bilinear transformation. Algebraically localized modes are derived by taking a Taylor expansion. Physically these equations will model the dynamics of water waves, where the dependent variable (typically the displacement of the free surface) can exhibit a sudden deviation from an otherwise tranquil background. Such modes are termed 'rogue waves' and are associated with 'extreme and rare events in physics'. Furthermore, elevations, depressions and 'four-petal' rogue waves can all be obtained by modifying the input parameters.